1990
DOI: 10.1177/1532673x9001800407
|View full text |Cite
|
Sign up to set email alerts
|

Human Rights and Foreign Aid

Abstract: Although President Carter spoke forcefully about the importance of human rights in his foreign policy, President Reagan disavowed such a claim. A number of scholars have gone beyond the rhetoric and estimated the relationship between foreign aid allocations and human rights in the two administrations; few have found significant differences. This research differs from past work by using data from all but two of the recipient countries of U.S. aid and by employing an incremental model of decision making to expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The threat succeeded. Multiple econometric studies show no correlation between American aid and the human rights regimes in recipient countries during this time period (Hofrenning 1990;Poe 1991;Stohl, Carleton, and Johnson 1984;Apodaca and Stohl 1999). Expectations of survival past 1980 were minimal.…”
Section: The Peace Corpsmentioning
confidence: 85%
See 1 more Smart Citation
“…The threat succeeded. Multiple econometric studies show no correlation between American aid and the human rights regimes in recipient countries during this time period (Hofrenning 1990;Poe 1991;Stohl, Carleton, and Johnson 1984;Apodaca and Stohl 1999). Expectations of survival past 1980 were minimal.…”
Section: The Peace Corpsmentioning
confidence: 85%
“…Haig also reversed course, declaring human rights would be a "major focus" of Reagan's foreign policy (Maynard 1989, 183).20 Second, under the Reagan administration several studies have found a statistical correlation between the amount of U.S. aid and the human rights conditions within the potential recipient countries (Cingranelli and Pasquarello 1985;Poe and Sirirangsi 1993). Indeed, the majority of these studies find that the significance of the statistical relationship increased from Carter to Reagan (Hofrenning 1990;Poe 1991Poe , 1992Apodaca and Stohl 1999). Buttressing the statistical findings are clear cases, such as Haiti or Chile, where the State department insisted on including human rights on the agenda in dealing with a particular country (Shultz 1993, 621, 971).…”
Section: The Peace Corpsmentioning
confidence: 99%